Efeito da chuva sobre a ação do herbicida imazapyr no controle de plantas daninhas aquáticas - de Campos, Caio Ferraz [UNESP]; de Souza, Guilherme Sasso Ferreira [UNESP]; Pereira, Maria Renata Rocha [UNESP]; Martins, Dagoberto [UNESP] (My University, 2010)
The aim of this study was to evaluate the influence of different periods of rainfall that occurred after the application of the imazapyr herbicide on the control efficiency of Pistia stratiotes and Eichhornia crassipes. We studied 10 mm rainfall, applied for 5' at different time periods (0h, 2h, 4h, 6h, 8h, 12h, 24h, not simulated rainfall) after the application of imazapyr formulation Arsenal NA, 250 g ai ha -1 (1.0 L cp ha -1). The experiment had completely randomized design with four replications. Plants were evaluated at 7, 14, 21, 28 and 35 days after application (DAA), and the results submitted to analysis of variance by F test and treatment means compared by Tukey's test (p <0. 05). The occurrence of rainfall up to 6 hours after herbicide application, plants of P. stratiotes, negatively affected its efficiency and control; rainfall intervals over 8 hours had no effect in control. The occurrence of rainfall at all time intervals did not affect the control of E. crassipes plants.

O objetivo deste estudo foi avaliar a influência de diferentes períodos de chuva ocorridos após a aplicação do herbicida imazapyr, em sua eficiência de controle sobre plantas de Pistia stratiotes e Eichhornia crassipes. Foram estudadas chuvas de 10 mm, aplicadas durante 5', em diferentes períodos de tempo (0h, 2h, 4h, 6h, 8h, 12h, 24h e não simulação de chuva) após a aplicação de imazapyr, na formulação Arsenal NA, a 250 g i.a. ha-1(1,0 L p.c. ha-1). O delineamento experimental utilizado foi o inteiramente casualizado, com quatro repetições. As plantas foram avaliadas visualmente aos 7, 14, 21, 28 e 35 dias após a aplicação (DAA), sendo os resultados obtidos submetidos à análise de variância pelo teste F e as médias dos tratamentos comparadas pelo teste de Tukey (p<0,05). A ocorrência chuvas em até 6 horas após a aplicação do herbicida imazapyr, em plantas de P. stratiotes, afetou negativamente sua eficiência de controle e, chuvas após intervalos acima de 8 horas não influenciaram no controle. A ocorrência de chuva em todos os intervalos de tempo, não interferiu no controle de plantas de E. crassipes.
Effect of rainfall on imazapyr action in aquatic weed control
Keywords: Chemical control; Phytotoxicity; Water hyacinth; Waterlettuce; aquatic plant; chemical control; herbicide; pesticide application; phytotoxicity; rainfall; variance analysis; weed control; Eichhornia; Eichhornia crassipes; Pistia stratiotes